EFFECT OF EXPOSURE TIME IN HOT WATER ON GERMINATION OF CANNABIS SEED - Arif Ullah (Policy Research Journal, 2025)
The experiment entitled “Effect of exposure time in hot water on germination of cannabis seed” was conducted in Plant Tissue Culture Laboratory, Department of Horticulture, The University of Agriculture Peshawar during the year 2022. The research was carried out in Completely Randomized Design (CRD) with three replications. For this experiment seeds of cannabis sativa (Baluchistan variety) were brought from Baluchistan Agriculture Research station. Those seeds were subjected to various exposure times e.g. Control (no treatment), 15min, 30min, and 45min in hot water at (50 oC) before culturing, and then the seeds were set to germinate in vivo condition. The seeds were examined for five days to record data on radicle and plumule emergence. The data showed maximum radical emergence (87%) at 15 min exposure time, and a similar response of (83%) radical emergence at 30 min exposure time while least radicle emergence (20%) is seen at 45 min exposure time. For control (60%) radicle emergence is noted. As plumule emergence is concerned, it emerged lately; the maximum plumule emergence (85%) was recorded for 30 min exposure time, while least plumule emergence (21%) was observed for 45 min exposure time. Control and 15 min exposure time behaved similarly giving (50%) and (52%) plumule emergence percentage respectively. It is concluded that hot water treatment has a significant effect on germination percentage of cannabis sativa seeds and 30 min exposure time at 50 degree centigrade must be given to cannabis sativa seeds in hot water treatment in order to raise maximum germination percentage.